Unlocking Intellectual Capital's Role in Enhancing Sustainable Financial Performance: A Study of Islamic Banks in Indonesia - Aini, Nurfina; Setiawan, Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study investigates the performance of intellectual capital (IC) within Islamic banks (IB) and evaluates its impact on sustainable financial performance. IC measurement employs the Modified Value-Added Intellectual Coefficient (MVAICâ„¢), an advanced model derived from VAICâ„¢. Data were gathered from 12 Islamic banks spanning the period 2012 to 2021. Empirical results reveal a significant positive relationship between IC and financial performance. Moreover, disaggregating the components shows varying degrees of association between IC components and IB financial performance indicators. Notably, efficient capital utilization and the effectiveness of human capital emerged as the most influential components of IC in this study. The findings contribute to a deeper understanding of IC and its role in the IB, offering valuable insights for stakeholders such as regulators and IB management to formulate pertinent strategies for creating, utilizing, and sustaining IC, thus fortifying the banking sector.